2020
DOI: 10.1519/jsc.0000000000003029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periodized vs. Nonperiodized Resistance Training on Army-Specific Fitness and Skills Performance

Abstract: Heilbronn, BE, Doma, K, Gormann, D, Schumann, M, and Sinclair, WH. Effects of periodized vs. nonperiodized resistance training on army-specific fitness and skills performance. J Strength Cond Res 34(3): 738–753, 2020—This study investigated the effects of periodized resistance training (PRD) and nonperiodized resistance training (NPRD) on army-specific fitness and skills performance measures. Forty-nine serving members of the Australian Army were randomly assigned to 1 of 3 training groups: PRD, NPRD, or no-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The arduous nature of the military service is well-known with soldiers expected to complete a range of occupational tasks [ 14 , 25 ]. Subsequently, physical training for the military must be extensive and robust to prepare the war fighter for both acute and chronic occupational physical demands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The arduous nature of the military service is well-known with soldiers expected to complete a range of occupational tasks [ 14 , 25 ]. Subsequently, physical training for the military must be extensive and robust to prepare the war fighter for both acute and chronic occupational physical demands.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review identified that non-traditional military physical training (i.e., advanced or structured resistance training programs) had a greater effect on performance across a range of fitness domains including occupationally specific tasks compared to traditional military physical training [ 14 ]. Furthermore, two recent studies in Australian Army recruits and soldiers have challenged the traditional bias in military physical training towards field expediency and shown it is possible to incorporate progressive resistance training into group training delivery models [ 25 , 31 ]. Such departures away from traditional, ‘one size fits all’ training regimes have also been noted in elite sport with individualised injury prevention training programs recommended [ 22 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Which periodization is better (traditional vs undulating) to induce changes in body composition and strength of healthy young adults? research protocol Heilbronn et al (2020). All subjects were familiarized with the testing procedures one week before.…”
Section: Methodsmentioning
confidence: 99%